Kinetic and Thermodynamic Studies of Chromium (VI) Sorption by Pure and Carbonized Fluted Pumpkin waste biomass (Telfairia occidentalis Hook F.) - Tarawou, Timi; Horsfall, Michael (Journal of Nepal Chemical Society, 2012)
The adsorption of chromium (VI) ions from aqueous solution was studied using pure and carbonized fluted pumpkin waste biomass (FPWB). The kinetic data shows a pseudo-first-order mechanism with rate constants of 1.26 × 10-2 and 1.933 × 10-2 mg g-1 min-1 for the pure and carbonized FPWB, respectively. While the pseudo-second-order mechanism has rate constants of 0.93 × 10-1 and 1.33 × 10-1 mg g-1 min-1 for the pure and carbonized waste biomass respectively. The pseudo-second order kinetic model was found to be more suitable for describing the experimental data based on the correlation coefficient values (R2) of 0.9975 and 0.9994 obtained for pure waste biomass (PWB) and carbonized waste biomass (CWB), respectively. The results obtained from this study show that PWB and CWB have very high removal capacity for chromium (VI) from aqueous solution over a range of reaction conditions. Thus, fluted pumpkin waste biomass (Telfairia occidentalis Hook F) is a potential sorbent for the treatment of industrial effluents containing chromium (VI) contaminant. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6436 J. Nepal Chem. Soc., Vol. 27, 2011 11-18 Uploaded date: 16 July, 2012